MAINTENANCE OF CAPITAL. - Sweeney, Henry W. (The Accounting Review, 1930)
This article focuses on different methods of maintaining capital may well be comprehensively examined and appraised. There are two main views on which maintenance of capital may be based. The first part of this article will briefly judge the more uncommon, less advantageous one. The second part will then evaluate the ramifications of the usual view. According to one viewpoint, the object in maintaining capital should be to preserve the same proportion of the total social capital as was possessed at the time the capital was originally invested. The second objection to relative maintenance of capital is that it is liable to prove unsafe as a practical basis. An ingenious plan that would automatically effect, among other purposes, maintenance of relative capital while utilizing the present system of money is that proposed by one economist. Under such a plan, intended to distribute productive shares in the economic process according to a standard of social justice and business progress would be adequately met by the existing price measuring-unit because changes in the general price level would tend to indicate a productivity change wherein the entire country both should and would share.